Peningkatan Kompetensi SDM Bidang F&B Service pada Usaha Makanan dan Minuman Di Kawasan Puncak Kab. Bogor - Vincent Sylvester Leewellyn; Nami Fitricia Pasaribu; Asep Syaiful Bahri (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2019)
ABSTRACTAccording to BPS West Java Province data, the number of visits in 2016 for foreign tourists to Bogor Regency in 2016 reached 228,913 and 4,955,079 for domestic tourists. This data shows that the level of tourist visits to Bogor Regency continues to increase. The increase in tourist arrivals should be supported by facilities and infrastructure and business tourism services including tourism services in the field of food and beverages. Based on 2016 BPS data, the number of Restaurants / Restaurants by Regency / City in West Java Province, 2013-2016 was 162 businesses. This might be said to be still lacking in terms of numbers, in terms of service quality it can be said to be still lacking because if it is seen that the employees working in the sector are mostly graduates of junior high and high school. To improve the ability of HR (employees) who work in the food and beverage business services sector, activities are needed that aim to increase the capacity of human resources (employees) of food and beverage businesses in Bogor Regency. Community service regarding the Improvement of Excellent Services Capability in Food and Beverage Enterprises in the Bogor Regency Peak Area was attended by 30 participants who were employees in the business of food and beverage tourism services who were directly selected by the Bogor Regency Culture and Tourism Service. Based on the results of this community service activity, the following conclusions can be drawn: the provision of knowledge and technology on improving management capabilities Capability of Excellent Services in Food and Beverage Enterprises in the Peak District. Bogor was well received by the participants and achieved the goals planned previously. This is indicated by the ability of participants to be able to understand and direct practice regarding service excellent. In addition, there were participants who after this training were appointed as supervisors at the restaurant where the participants worked.Keyword: Competence of HR in F & B Service, Food and Beverage Business                                                                                                                                             ABSTRAKMenurut data BPS Provinsi Jawa Barat, jumlah kunjungan pada tahun 2016 untuk wisatawan mancanegara ke Kabupaten Bogor pada tahun 2016 mencapai 228.913, dan 4.955.079 untuk wisatawan nusantara. Data ini menunjukkan bahwa tingkat  kunjungan wisatawan ke Kabupaten Bogor terus meningkat. Peningkatan kunjungan wisatawan ini mestinya didukung oleh sarana dan prasarana dan usaha jasa wisata termasuk didalamnya adalah usaha jasa wisata dibidang makanan dan minuman. Berdasarkan data BPS 2016 jumlah Restoran/Rumah Makan Menurut Kabupaten/Kota di Provinsi Jawa Barat, 2013-2016 adalah sebesar 162 usaha. Hal ini mungkin bisa dikatakan masih kurang dari segi jumlahnya, dari segi kualitas layanan dapat dikatakan masih kurang karena jika dilihat bahwa karyawan yang bekerja di sektor tersebut sebagian besar merupakan lulusan SMP dan SMA. Untuk meningkatkan kemampuan para SDM (karyawan) yang bekerja di sektor jasa usaha makanan dan minuman tersebut, maka dibutuhkan kegiatan yang bertujuan untuk meningkatkan kapasitas SDM (karyawan) usaha makanan dan minuman di Kabupaten Bogor. Pengabdian kepada masyarakat mengenai Peningkatan Kemampuan Services Excellent pada Usaha Makanan dan Minuman Di Kawasan Puncak Kabupaten Bogor diikuti oleh 30 peserta yang merupakan karyawan di bidang usaha jasa wisata makanan dan minuman yang dipilih langsung oleh Dinas Kebudayaan dan Pariwisata Kabupaten Bogor. Berdasarkan hasil kegiatan Pengabdian masyarakat ini, maka dapat ditarik kesimpulan sebagai berikut: pemberian ilmu pengetahuan dan teknologi mengenai peningkatan kemampuan pengelolaan Peningkatan Kemampuan Services Excellent pada Usaha Makanan dan Minuman Di Kawasan Puncak Kab. Bogor diterima dengan baik oleh para peserta dan mencapai tujuan yang sudah direncanakan sebelumnya. Hal ini ditandai dengan kemampuan para peserta untuk dapat memahami serta praktek langsung mengenai service excellent. Selain itu,  terdapat peserta yang setelah pelatihan ini diangkat menjadi supervisor di restoran tempat peserta itu bekerja.Kata Kunci: Kompetensi SDM Bidang F&B Service, Usaha Makanan dan Minuman.